PERSEPSI, PREFERENSI DAN POLA KONSUMSI MAKANAN JAJANAN BERBASIS SINGKONG TERHADAP REMAJA : KASUS DI SMAN 2 BANDAR LAMPUNG DAN SMAN 1 TUMIJAJAR TULANG BAWANG BARAT - Tania Oktrisa; Wuryaningsih Dwi Sayekti; Indah Listiana (Lampung University, 2015)
The aim of this research were to determine perceptions, preferences and consumption pattern and the factors that affected the consumption of cassava snacks by teenagers. This research used survey method. The sampling technique used in this research was Simple Random Sampling. Respondents were 35 students of SMAN 2 Bandar Lampung and 37 students of SMAN 1 Tumijajar. The data were analyzed by quantitative description and verification analysis. The results showed that students's perception of the cassava snacks price, availability of cassava snacks, appearance and image of cassava snacks were considered normal. The students generally preferred cassava snacks with spicy flavor, strong cassava aroma and crunchy texture. The most preferred form of cassava snacks was chips. During a month, teenagers got energy from cassava snacks that the average is 86 kcal/day for teenagers in Bandar Lampung and 75 kcal/day for teenagers in Tumijajar. The average consumption frequence of cassava snacks by teenagers in Bandar Lampung is 1-2 times per month and 3-4 times per month by teenagers in Tumijajar. Type of cassava snacks that was consumed during the past month was cassava chips, klanting, combro, and tela-tela. Cassava snacks were obtained by purchasing in the shop or in the market, self cooking, and or providing by others. The factors that influence food consumption of cassava snacks are household income, number of teens allowance, environment gender and preferences. The higher of household income and allowance teenagers will make the consumption of cassava snacks greater. Key words: cassava snacks, consumption pattern, perception, preference, teenagers